Nanowastes riscos para saúde humana e meio ambiente: diálogos entre o princípio da precaução e a sociedade de risco - Liziane Paixão Silva Oliveira; Maria Edelvacy Marinho; Ellen de Oliveira Fumagali (Araucaria)
Nanotechnology is a branch of science that has developed over the past decades, with applications in several key areas: health, energy, electronics, clothing, environment, among others. Increased production and consumption of nanoproducts has entailed expanding the amount of nanowastes in the environment. However, little has been discussed about the impacts of these wastes into the environment, the health of people, animals and plants. Because of the scientific uncertainties the application of the precautionary principle is a subtle instrument that allows the management of risks caused by nanotechnologies. On the other hand, seeks to assess the ecological dangers in the contours of the Risk Society, in relation to the precepts established by Ulrich Beck and Niklas Luhmann.